2011
DOI: 10.1093/humrep/der301
|View full text |Cite
|
Sign up to set email alerts
|

An imbalance in interleukin-17-producing T and Foxp3+ regulatory T cells in women with idiopathic recurrent pregnancy loss

Abstract: Enhanced pro-inflammatory immune responses with suppressed immune regulation may be an important immune mechanism involved in RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 39 publications
8
138
1
1
Order By: Relevance
“…9,52,61,64,70 In 2004, Sasaki et al 61 first reported the association between regulatory T cells and spontaneous abortion. CD4 + CD25 high regulatory T cells in the peripheral blood and deciduas decreased in spontaneous abortion group as compared to induced abortion group.…”
Section: Regulatory T and Th17 Cells In Women With Rplmentioning
confidence: 99%
See 1 more Smart Citation
“…9,52,61,64,70 In 2004, Sasaki et al 61 first reported the association between regulatory T cells and spontaneous abortion. CD4 + CD25 high regulatory T cells in the peripheral blood and deciduas decreased in spontaneous abortion group as compared to induced abortion group.…”
Section: Regulatory T and Th17 Cells In Women With Rplmentioning
confidence: 99%
“…[5][6][7] In addition, an increased population of CD4 + Th1 cells is also thought to be harmful in early pregnancy. [8][9][10] Recent advances in immunologic studies have widened our knowledge of how the immune response is regulated. Regulatory T cells are considered the most important immune regulator, especially in the peripheral immune system.…”
Section: Introductionmentioning
confidence: 99%
“…P 4 promotes Th2-type cytokine production, while suppressing Th1-type cytokine production, resulting in a Th2-type immunity skew (Miyaura and Iwata, 2002). Recently, it has been reported that despite the regulatory effect of P 4 on the Th1/Th2 paradigm, P 4 also modulates the Th17/Treg paradigm by promoting the polarization of Treg cells and inhibiting the polarization of Th17 cells (Lee et al, 2011a(Lee et al, , 2011b. Additionally, it has been shown that the regulatory effect of P 4 on the Th1/Th2/ Th17/Treg paradigm can be blocked by the receptor antagonist, RU486, indicating the participation of the Th1/Th2/Th17/Treg paradigm in RU486-induced abortion (Nautiyal et al, 2004;Mao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 11 recently published an investigation that studied pro-inflammatory cytokines (TNF-a, IFN-c, and IL-17), anti-inflammatory cytokine IL-10, and Foxp3 in the peripheral blood mononuclear cells of idiopathic women with RIF. Mariee et al 12 revealed an altered expression of leukaemia inhibitory factor and IL-15 in the endometrium of women with RIF.…”
Section: Discussionmentioning
confidence: 99%